Mengapa Penyembuhan Diri Sendiri dapat dilakukan? Etnografi Pemanfaatan Tanaman Obat Keluarga dan Pola Pencarian Kesembuhan pada Masyarakat Aceh - Ibrahim Chalid; Ade Ikhsan Kamil; Faizul Aulia; Rasyidin Rasyidin; Fitri Yanti (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2023)
The pattern of seeking healing and the use of family medicinal plants today has become an inseparable part of people's lives. In social life, illness becomes a discourse on the interaction of human life with nature. The disease suffered by the community is not only a challenge in itself, but they have the knowledge of healing, so that the illness can be handled independently or through the role of assistants in traditional ways. This study seeks to document the various knowledges of the community in the use of plants that can cure disease and also to map the pattern of seeking healing that is believed by the people of Aceh. Through an ethnographic qualitative approach, this research uses interviews and direct observation in two areas in Aceh. The results of the study show that the Acehnese living in the two areas have their own knowledge to obtain a cure for their illness. The knowledge was collected based on the response to illness through the role of traditional healers and the transmission pattern of treatment knowledge from generation to generation to medicinal plants, so that in obtaining healing, they were able to survive with the conditions they experienced until they obtained complete healing.